2014
DOI: 10.1016/j.pec.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a group-based intervention to change medication beliefs and improve medication adherence in patients with rheumatoid arthritis: A randomized controlled trial

Abstract: Absent intervention effects might have been due to, amongst others, selection bias and a suboptimal treatment integrity level. Hence, targeting beliefs about medication in clinical practice should not yet be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 45 publications
1
57
1
1
Order By: Relevance
“…Similar improvement in medication adherence and disease activity was reported by many authors in the intervention group compared with the control group 27,30,31 . This was in contrary to a recent study which tested the effect of a motivational interviewing programme on medication adherence in RA patients and did not demonstrate any significant change to patient beliefs about medications or in improving medication adherence and this may be due to focusing on patient-related factors only 32 . Other interventional studies failed to improve medication adherence were reported 33,34 .…”
Section: Discussioncontrasting
confidence: 99%
“…Similar improvement in medication adherence and disease activity was reported by many authors in the intervention group compared with the control group 27,30,31 . This was in contrary to a recent study which tested the effect of a motivational interviewing programme on medication adherence in RA patients and did not demonstrate any significant change to patient beliefs about medications or in improving medication adherence and this may be due to focusing on patient-related factors only 32 . Other interventional studies failed to improve medication adherence were reported 33,34 .…”
Section: Discussioncontrasting
confidence: 99%
“…One study 59 did not find that targeting beliefs about medication had any effect on DMARD adherence. Another study 60 found that supplying a nonadherent patient's rheumatologist with a report about medication use and adherence did not change adherence or the patient's beliefs about medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The most common limitations reported by authors regarding threats to validity were: generalizability, inclusion of subjects with high adherence at baseline, 18,20,24,25,28,30,31 lack of statistical power, 15-19, 28, 30, 32 and recall bias and social desirability for studies reporting only self-reported measures 16,23 and including only subjects with low adherence leading to a recruitment challenge. 17 The authors offered adequate explanations on how they dealt with these limitations with the exception of social desirability, which remains as a possible source of bias for those two studies.…”
Section: Quality Of the Studies And Evaluation Of Biasmentioning
confidence: 99%